The Effect of Growth Mindset on Athletic Learning Success: A Study on Students in Sprint Numbers - Sutiswo; Wahyu Saputra; Mochamad Fajar Permana; Asep Akbaruddin; Tika Fitriani; Puspa Hanuraeni (Journal of Physical and Outdoor Education, 2025)
This study aims to analyse the effect of growth mindset on the success of athletic learning, especially in sprinting numbers on PJKR STKIP Pasundan students. The method used is Single Subject Research (SSR) with A-B-A design according to Tawney and Gas (1984), initial measurement (pre-test), growth mindset-based intervention phase, and final measurement (post-test). The research subjects were 34 students of Physical Education, Health, and Recreation (PJKR) STKIP Pasundan who were selected through cluster random sampling technique. The instruments used included a sprint test and a growth mindset questionnaire. The results showed a significant increase in students' sprint performance after the growth mindset intervention. Before the treatment, the majority of students were in the low ability category (71%), but after the intervention, this proportion decreased to 24%, while the fair and good categories increased to 56% and 20%. Statistical tests using paired sample t-test showed a significant difference between the pre-test and post-test results (t = 9.781, p = 0.001). The data also showed a strong and significant relationship between growth mindset and sprint performance (r = 0.794, p < 0.001). Thus, the growth mindset-based intervention proved to be effective in improving the success of students' sprint learning. Keywords.: Growth Mindset, Sprint, Athletics Learning.